Blender to Unreal Engine 5 : 3D props. (Packt Publishing, 2022)
Learn how to create a triple AAA grade medieval windmill 3D model using Blender as part of medieval game assets and learn to export them to Unreal Engine 5 About This Video 3D modeling from beginner level right up to techniques used by professionals around the world Animating a structurally accurate medieval waterwheel Animations and key commands are shared throughout the learning process In Detail In this course, we will be creating a medieval windmill, an intricate medieval asset requiring mechanical knowledge full of life through 3D animation. Our focus will be on creating realistic and fully functional subcomponents for our windmill, which will include an intricate set of wooden supports, balconies, stairs, a waterwheel, and windmill arms. You will learn how to use keyframes to key in different animations to the parts we want to animate. These will include our medieval windmill's waterwheel, windmill arms, and windmill sign. Next, you will learn how to take control of your scene's aesthetics through an HDRI system for lighting. You will also learn how to create your own materials using the shared textures and learn all about the gamma, hue, saturation, and some world Blender nodes. Finally, we will deep dive into Epic's all-new Unreal Engine 5. You will learn everything, right from importing animations from Blender to having them work correctly in Unreal Engine 5 to render in real-time and creating our own portfolio gradient skybox! By the end of this course, you will be able to create your own 3D medieval windmill asset for your game. Audience This course is designed for beginner and mid-level 3D modelers, who want to learn how to build medieval-themed AAA game-ready assets such as a fully animated medieval windmill with Blender.